2001
DOI: 10.1159/000050578
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Tuberculosis in Patients with Diabetes mellitus

Abstract: Background: Diabetes mellitus has been reported to modify the presenting features of pulmonary tuberculosis, but there are varying data, particularly regarding the association with lower lung field involvement. Objectives: To determine whether diabetes mellitus alters the clinical and radiographic manifestations of tuberculosis in nonimmunocompromised hosts and to define the determinants of lower lung field involvement. Methods: A retrospective review of the records of all patients with tuberculosis and diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
98
4
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 6 publications
(14 reference statements)
16
98
4
9
Order By: Relevance
“…19,20 The association between diabetes mellitus and TB has been well documented, and some studies report that smear-negative PTB is more common in people with diabetes, although this association may require rigorous studies to prove an association. [21][22][23] Information on diabetes mellitus was not collected during the study, and the association may warrant further research. In addition, knowledge, attitudes and behaviour of programmatic staff may infl uence the practice of diagnosing smear-negative PTB.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The association between diabetes mellitus and TB has been well documented, and some studies report that smear-negative PTB is more common in people with diabetes, although this association may require rigorous studies to prove an association. [21][22][23] Information on diabetes mellitus was not collected during the study, and the association may warrant further research. In addition, knowledge, attitudes and behaviour of programmatic staff may infl uence the practice of diagnosing smear-negative PTB.…”
Section: Discussionmentioning
confidence: 99%
“…reported a mean ESR of 71.5 mm/h. (10) In a sample of 109 pulmonary tuberculosis patients, 38.5% of whom were co-infected with HIV, Dominguez-Castellano e al. reported a mean ESR of ≈65 mm/h.…”
Section: Discussionmentioning
confidence: 99%
“…(4,7,10,11) Although cavitation is the most widely reported chest X-ray finding in patients with PTB, the reported rates range from very low (in studies involving HIV-infected or otherwise immunocompromised patients, children, or the elderly) to very high (in patients with concomitant diabetes). (7,(9)(10)(11)23) Among patients with reactivation tuberculosis, cavitary lesions are reported to occur in 28-82%, the mean being 40-50%. (6,9,11,20,24) Kartaloglu e al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A study done by Anand K Patel et al, which showed radiographic presentation of patients of pulmonary TB with DM showed higher involvement of lower lung field 84% when compared to upper lung field and cavitary lesions, more frequently confined to lower lung field. 22 A study done by Bokam et al showed that 59% had involvement of only lower lung fields, 29.5% upper lung fields and 11.3% had involvement of both upper and lower lung fields. 20 Another study done by Avuthu etal showed that patients with poor glycemic control are likely to have lower lung field involvement and cavitary disease on chest radiograph.…”
Section: Sputummentioning
confidence: 97%